Personification of antihypertensive therapy in ischemic cerebral stroke - Dariy, V. I.; Serikov, K. V.; Kmyta, O.; Rybalko, T. P.; Kolesnyk, O.; Дарій, Володимир Іванович; Серіков, Костянтин Вікторович; Рибалко, Тетяна Петрівна (My University, 2024)
The purpose of the study is to optimize monitoring and personalize antihypertensive therapy in patients with severe ischemic cerebral stroke (ICS). We examined 37 patients with ICS, average age 74,1±1,3 years, who received treatment in intensive care wards of the stroke department with general neurology beds of the Municipal Non-Profit Enterprise “City Hospital № 9” of the Zaporizhzhia City Council. There were 16 men (43,2%), average age 71,9±2,1 years; women – 21 (56,8%), average age 75,8±1.6 years. Personification of antihypertensive therapy for severe ICS was carried out based on the etiology of hypertensive hemodynamic disorders: hyperkinetic type of arterial hypertension (Cardiac index ≥ 3,80 L×min-1×m-2) or hypokinetic type of arterial hypertension (Cardiac index ≤ 2,98 L×min-1×m-2). In patients with severe ICS and hyperkinetic type of arterial hypertension, initial hemodynamic parameters were characterized by Mean arterial pressure (MAP) of 111,4 ± 1,4 mm Hg; Heart rate (HR) of 107,2±1,6 min; Cardiac index (CI) 6,74±0,27 L×min-1×m-2; the Total peripheral vascular resistance (TPVR) is 674±36 dyn×sec-1×cm-5. For the purpose of antihypertensive correction of the hyperkinetic type of arterial hypertension (CI ≥ 3,80 L×min-1×m-2), a solution of Magnesium Sulfate was used intravenously at a dose of 2500-5000 mg×day-1 in combination with Bisoprolol 5-10 mg×day-1 orally. This made it possible to stabilize hemodynamic parameters by the end of intensive therapy within the limits of eukinetic values: MAP 95,2 ± 1,5 mm Hg (p < 0,05); HR 81,9 ± 1,5 min (p < 0,05); CI 3,60±0,15 L×min-1×m-2 (p < 0,05); TPVR is 1079±58 dyn×sec-1×cm-5 (p < 0,05). In patients with severe ICS and hypokinetic type of arterial hypertension, initial hemodynamic parameters were characterized by MAP of 117,7 ± 2,8 mm Hg; HR of 76,7 ± 1,5 min; CI 2,74±0,18 L×min-1×m-2; TPVR is 1754±123 dyn×sec- 1×cm-5. For the purpose of antihypertensive correction of the hypokinetic type of arterial hypertension (CI ≤ 2,98 L×min- 1×m-2), a solution of Ebrantil was used intravenously as a bolus of 1,25-2,5 mg with a further infusion of 5-40 mg×hour-1. This made it possible to stabilize hemodynamic parameters by the end of intensive therapy within the limits of eukinetic values: MAP 92,7 ± 1,7 mm Hg (p < 0,05); HR 81,4 ± 0,9 min (p < 0,05); CI 3,65±0,16 L×min-1×m-2 (p < 0,05); TPVR is 1036±46 dyn×sec-1×cm-5 (p < 0,05).
Keywords: ischemic cerebral stroke; hyperkinetic type of arterial hypertension; hypokinetic type of arterial hypertension; antihypertensive personalized therapy